Method of Improving Stability of a Highly-Loaded Axial Compressor Stage by Coupling Different Casing Treatments - Y. Chen; A. Lin; H. Zhang; W. Chu (Journal of Applied Fluid Mechanics, 2022)
Casing treatment is a powerful method for improving the stability of aircraft compressors. An optimized slot-type casing treatment was tested on the first rotor of a highly-loaded two-stage compressor, and the results showed that the casing treatment could not increase the compressor stability at the design and off-design speeds. A coupled casing treatment (CCT), which is built with an injector, a bridge, a plenum chamber, and several slots for a recirculating loop, is proposed and optimized to enhance the stability of the compressor in the present study. The optimized CCT improves the compressor stability and efficiency under the design condition by 75.8% and 0.71%, respectively. The coupling effect, which is established with an inner circulation in the slots and an outer circulation from the slots to the injectors, accounts for the excellent stability enhancement. The coupling effect reduces the amount of tip leakage flow, depresses the development of the tip leakage vortex (TLV), and greatly decreases the blockage in the rotor tip which is primarily induced by the interaction of the shock-wave and boundary-layer at the blade suction surface. The parametric study shows that improving the coupling effect has a positive effect on reducing the rotor tip blockage, but a negative effect on the stability of the compressor stage. This is because the inflow condition of the stator is tremendously distorted while the coupling effect is excessively strong, which can cause a stall in the stator rather than in the rotor. The compressor stability can be maximally enhanced by adjusting the strength of the coupling effect to make a compromise of the improved rotor tip flow and the deteriorated stator flow.